DINAMIKA HUBUNGAN ANTARA AGAMA LOKAL, AGAMA RESMI, DAN NEGARA - Arafat Noor Abdillah; Syafira Anisatul Izah (Mukaddimah: Jurnal Studi Islam, 2022)
Discrimination against local religions frequently imposes stigmas on Indonesian society, resulting in long-term trauma for their adherents. This does not always result from the perpetrators or the religious practices they perform. Religious institutions and associative organizations that can be formalized by using adherents of certain religions have a huge hand in the dynamics of inter-religious relations. This function cannot be separated from religious elites who have religious authority and create their own personal privileged space to determine collective settlement on the production and reproduction of religious values and teachings, potentially creating problems in religious construction. The writer analyzes this problem with a structural-functional paradigm of the way state rules on serving local religions that used to be discriminatory have been modified. This study aims to look at assumptions based on social stigma towards adherents of local religions and find a resolution to these problems. Its goals are to enhance understanding of the practices of beliefs and local cultural ancestral wisdom, form inclusive religious awareness, and construct positive and moderate inter-religious relations in Indonesia. The consequences show that discrimination in opposition to local religions can be reduced by tightening the socialization of government policies via the participation of religious institutions and associative agencies. Keywords: Local religions, religious institutions, government policies.